Changes in the pulmonary surfactant in patients with mild to moderate COVID-19. - Spela Kokelj; Per Larsson; Emilia Viklund; Hatice Koca; Hanna Slogén; Lowie Vanfleteren; Bo Nilsson; Karin Fromell; Johan Westin; Anna-Carin Olin (PLoS ONE)
Introduction Changes in the pulmonary surfactant have been seen in severe COVID-19, but data on mild to moderate COVID-19 is scarce. The aim of this study was to explore the protein and phospholipid profiles in the small airways in patients with mild to moderate COVID-19. Methods 29 cases with COVID-19 and 17 healthy controls were examined at baseline. 22 cases were re-examined at follow-up after recovery from COVID-19. Airwave oscillometry was performed and the biological material from the respiratory tract lining fluid was collected with the PExA (Particles in Exhaled Air) method. SOMAscan was used for the analysis of proteins, and liquid chromatography with tandem mass spectrometry (LC-MS/MS) for phospholipids. Results 95 lipid species belonging to 8 lipid classes, and 46 proteins were analysed. Relative amounts of 13 lipid species differed between cases and controls at baseline, and of 24 lipid species at follow-up. At follow-up, the phosphatidylethanolamine class (PE) was significantly lower in cases at than in controls, and a significant decrease in PE, as well as a change in 20 lipid species from baseline to follow-up in cases was seen. The protein profile did not differ between cases and controls either at baseline or follow-up, or between repeated measurements in cases. Conclusions The observed alterations in the surfactant phospholipids in the RTLF indicate that surfactant homeostasis is affected already in mild to moderate COVID-19, and these changes appear to persist over time.